Cartografía Táctil para la Enseñanza de los Pisos Bioclimáticos a Estudiantes en Condición de Ceguera y Baja Visión del Grado Cuarto en el Colegio José Félix Restrepo en Bogotá. (2020)
The objective of this document is to present a methodological proposal for teaching bioclimatic floors to blind students in the fourth grade of the José Félix Restrepo School in Bogotá. Thus, it addresses elements of the process to create a material by taking into account components of Tactile Mapping. This resource has proven to be effective in different teaching contexts in Latin America. The route proposed throughout the text provides information linked to epistemological, theoretical and methodological aspects related to the investigative process that was carried out throughout the creation of the Teaching Material. The results show the importance that teaching materials favor inclusion processes for people with visual disabilities in regular teaching classrooms. In the same way, highlights the importance of creating materials that respond to specific training needs from a pedagogically situated perspective is recognized.